False data detection in mobile ad-hoc network based on digital signature - Abarghouei, Babak Emami (2013)
Routing misbehavior and false communication on wireless sensor network are so significant. An attacker can devour the sensor resources. No central monitoring system, lead to mobile sensor network suffering false communication. This thesis, organized to introduce a new detection method to mitigate the effect of false data on the mobile AD-HOC network. DNACK, which proposed in this thesis, Is a new modification of NACK method. DNACK also consider about negative acknowledgment to find the false route messages. DNACK can detect modified messages in the middle of a route in oppose of NACK which, can detect false modified data on the destination. By comparison, the Delivery percentage on NACK and DNACK, DNACK shown better results in opposed to NACK method. Simulation has been done in three modes of node’s mobility Speed in meter per second (M:0 , M:5 and M; 10 ). In all situations, the efficiency of DNACK is better than NACK because in NACK nodes all packets (original and modified) are delivering to destination by contrast in DNACK just original packets are deliver to destination. However the Delivery percentage in NACK is Higher than DNACK which is around 2% for 10 meters per second nodes’ movement .Nevertheless DNACK is more efficient than NACK .On M=10 (m/s) DNACK shown 64% verified messages on Destination in opposed by 60% verified messages on NACK method. In overall the efficiency of packet delivery can be calculated by multiplication of overall delivery by verified packet shows that DNACK method has 51.5 % verified messages delivery in opposed of NACK by 49.8 % delivery on M=10 m/s.